2019
DOI: 10.4136/ambi-agua.2375
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cloud condition on Sentinel-2 MSI and Landsat-8 OLI images of a public supply lake in Belém-Pará-Brazil

Abstract: The eutrophication process leads to reduced water quality and economic losses worldwide. Furthermore, it is possible to apply remote sensing techniques for monitoring of aquatic environments. In this paper, we analysed the combined use of Sentinel-2 Multispectral Instrument and Landsat-8 Operational Land Imager data to monitor a eutrophic aquatic environment under adverse cloudy conditions, from July 2016 to July 2018. Data pre-selection was performed, and then the images were acquired for further investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recent research in many parts of the world involving water quality have made use of data from Landsat-8 (Liu, Wang, 2019, González-Márquez et al, 2018, Mushtaq, Nee Lala, 2017, Sentinel-2 (Karaoui et al, 2019, Potes et al, 2018 or both (Dutra et al, 2019, Yadav et al, 2019, Watanabe et al, 2018. Table 1 gives a list of some of these authors with the sensor they used and the parameters they analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in many parts of the world involving water quality have made use of data from Landsat-8 (Liu, Wang, 2019, González-Márquez et al, 2018, Mushtaq, Nee Lala, 2017, Sentinel-2 (Karaoui et al, 2019, Potes et al, 2018 or both (Dutra et al, 2019, Yadav et al, 2019, Watanabe et al, 2018. Table 1 gives a list of some of these authors with the sensor they used and the parameters they analysed.…”
Section: Introductionmentioning
confidence: 99%
“…In one previous analysis in the study area, Tavares, Dutra, et al, 41 found that the Normalised Difference Vegetation Index (NDVI) could dissociate different types of vegetation better than other straight vegetation indices, such as the Normalised Difference Water Index (NDWI). For this reason, we adopted the NDVI to interpret the vegetation classes.…”
Section: Vegetation Classes and Radiometric Indicesmentioning
confidence: 97%
“…These indices utilize the reflectance and absorptive properties of snow in visible, NIR, and SWIR bands [29,35,[38][39][40][42][43][44][45][46][47].Although these indices have been frequently used for snow cover mapping with various multispectral satellite datasets and proven their significance in extracting snow cover in different terrain conditions, water and cloud are two major impurities that pose as a challenge in extracting snow pixels from space-borne multispectral sensors. A series of studies have been conducted for developing a masking technique or improved indices [48][49][50][51] for removing the impact of cloud pixels, but there are a sufficient number of studies [29,37,[52][53][54][55][56] that have shown that water pixels are always misunderstood as snow when extracted with these indices. Thus, there is an additional requirement of a filtering technique for precise delineation of snow cover with available index-based techniques.In this study, we propose a new snow cover index named the snow water index (SWI).…”
mentioning
confidence: 99%